Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5455/cap.20130512
|View full text |Cite
|
Sign up to set email alerts
|

An Overview On Melatonin Hormone

Abstract: ÖZETMelatonin hormonu, son yıllarda tüm dünyada gittikçe artan bir ilgiyle araştı-rılmaktadır. Ana görevi vücudun biyolojik saatini koruyup ritmini ayarlamak olan melatonin, vücudun birçok biyolojik ve fizyolojik süreçlerinde yer alır. Hücrelerin yenilenmesi, bağışıklık siteminin güçlenmesi, uyku ritminin ve vücut ısısının düzenlenmesi diğer önemli görevleri arasındadır. Lipofilik özel-liği nedeniyle bilinen en güçlü antioksidandır. Bu özelliği sayesinde tüm vücut alanlarına ulaşabilmekte ve kan-beyin bariyeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…It should be remembered that there may be errors in the regulation of treatments, as well as an increased risk of self-injury in healthcare workers. It can be argued that the risk of injury to patients or healthcare workers will be higher for the night-shift group in our study, given the longer duration of the night-shift in our study (16 hours) compared to the duration of the night-shift (12 hours) in the study by Thompson et al 14 The imbalance of melatonin levels are known to be involved in the etiology of depression 15,16 . A study of hormonal changes reported a decrease in melatonin levels and an increase in inflammatory markers in nightshift workers 17,18 .…”
Section: Discussionmentioning
confidence: 55%
“…It should be remembered that there may be errors in the regulation of treatments, as well as an increased risk of self-injury in healthcare workers. It can be argued that the risk of injury to patients or healthcare workers will be higher for the night-shift group in our study, given the longer duration of the night-shift in our study (16 hours) compared to the duration of the night-shift (12 hours) in the study by Thompson et al 14 The imbalance of melatonin levels are known to be involved in the etiology of depression 15,16 . A study of hormonal changes reported a decrease in melatonin levels and an increase in inflammatory markers in nightshift workers 17,18 .…”
Section: Discussionmentioning
confidence: 55%
“…Melatonin is a neuroendocrine hormone that affects the growth, and reproduction of mammals ( 73 , 74 ). During the night (especially between 11:00 p.m. and 5:00 a.m.), blood melatonin levels increase 3-10 times and the secretion of melatonin peaks ( 75 ). Mice lacking melatonin receptors (such as MT1) had slightly higher daytime activity than mice without melatonin receptors deficiency ( 76 , 77 ), which suggests that melatonin may influence activity rhythms by acting on receptors.…”
Section: Discussionmentioning
confidence: 99%